INDICATIONS FOR REMOVAL OF MANDIBULAR THIRD MOLARS - A RETROSPECTIVE INSTITUTIONAL STUDY - Kalyani. P,; M. P. Santhosh Kumar, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The extraction of a third molar is one of the most commonly performed procedures in oral surgery. The indications include caries, pericoronitis, for orthodontic treatment & prophylactic removal. The aim of this study was to determine the different indications for extraction of third molars of mandible in dental patients. This retrospective study involved analysis of case records of all patients who underwent extraction of mandibular third molars from June 2019 to April 2020 in our institution. Our study sample consisted of 1462 patients, and data tabulation was done based on the following parameters: age, gender, tooth Number and indications for extraction. Statistical analysis was done using SPSS Version 20.0, and results obtained. Categorical variables were expressed in terms of frequency and percentage. Chi-square test was used for testing associations between categorical variables and p-value <0.05 was considered statistically significant. The extraction of mandibular third molar showed slightly higher prevalence in females (51.2%) with a female - to - male ratio of 1.05 : 1. Highest prevalence of extractions was observed in the age group of 21-30 years [25.0%] followed by 31-40 years [24.6%]. Caries was the most predominant indication for extraction of mandibular 3rd molars [66.0%] in our study population. There was a statistically significant association present between age and indications for extractions of mandibular third molar [p<0.001]; and gender and indications for extractions of mandibular third molar. [p < 0.001]. Within the limits of the study, it was concluded that, extraction of mandibular third molars was more prevalent among females than males. Higher prevalence of mandibular third molar extractions was observed in patients in their third decades of life. Caries was the most common indication for extraction of mandibular third molars in our study population. Pericoronitis is the common indication for mandibular third molar extraction in the younger age group and dental caries is the common reason for removal in the middle age group, while periodontitis is the common cause for removal of mandibular third molars in the elderly people.